Dietary inclusion of fibrous corn silages reduces gastric mucosa damage in fattening heavy pigs - M. Spanghero; M. Braidot; M. Orioles; C. Sarnataro; I. Pividori; A. Romanzin (Porcine Health Management)
Abstract Background Several surveys conducted at slaughter sites have highlighted that gastric lesions are a widespread issue in fattening pigs, mainly due to feeding regimes. Diets with small particle sizes and low fibre contents guarantee high digestibility and performance but generate more rapid stomach emptying with a negative effect on gastric mucosa integrity. Providing fattening pigs with fibrous materials (e.g., straw provided in racks) or coarse fibrous ingredients (e.g., coarse silages) reduced the presence of gastric ulcers. The present research compares a traditional corn-soy-based diet with an experimental diet where bran and a portion of corn meal was substituted with whole ear and whole plant corn silages at the maximum dosages permitted by new Protected Designation of Origin for Italian dry-cured ham (20 and 10% of DM, respectively). This study aimed to examine the impact of the inclusion of corn silages in the diet on the productive performance of heavy Italian pigs and their ability to mitigate gastric mucosa damage. Results The growth performances were satisfactory (750–800 g/d) given the advanced interval of growth of animals (from 120 to 180 kg). However, the inclusion of corn silages tended to reduce the growth rate by 5–6% due to the reduction of organic matter digestibility, without compromising the slaughter traits or the back-fat fatty acid profile. The experimental diet substantially affected both stomach development and mucosal integrity. The first consequence was an increase in stomach weight of approximately 6% (P < 0.01) but the most notable advantage of coarse feeding was a reduction in stomach damage severity, with a low number of cases with higher scores in animals fed coarse materials (P < 0.01). Conclusions The dietary inclusion of corn silages (30% of diet DM) decrease effectivelly the severity of stomach damage in finishing heavy pigs. Based on the feeding trial performances, the perspective of feeding heavy pigs corn silage should consider specific agronomic and harvesting techniques to improve digestibility and not reduce the growth rate.